Deposit Insurance and Bank Liquidity: Does Ownership Structure Matter? - Trinugroho, Irwan; Muthmainah, Muthmainah; Ariefianto, Mochammad Doddy; Sutaryo, Sutaryo (UI Scholars Hub, 2016)
We examine how the level deposit insurance coverage affects bank liquidity. We also test the role of ownership in the relationship between deposit insurance coverage and bank liquidity. This study uses quarterly data of Indonesian banks from Q1:2002 - Q2:2008. We argue that the presence of explicit deposit insurance changes a bank‘s behavior in liquidity management in the form of decreasing asset liquidity. We find some evidence on the negative impact of deposit insurance coverage on bank liquidity. However, little is found on the role of ownership structure. The credibility of deposit insurance system and implicit guarantee are the main policy implications.